2014
DOI: 10.1007/s12562-014-0740-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of cis-7-icosenoic acid in the lipids of Japanese marine fish, shellfish, and crustaceans

Abstract: This paper reports the concentration and composition of the isomers of cis-icosenoic 26 acid (20:1) in the fatty acids of various species of Japanese marine animals. The main purpose 27 of this study is to reveal the distribution of a positional isomer, cis-7-20:1 (c7-20:1), in marine 28 animals. Because this isomer overlaps with the c9-20:1 isomer in gas chromatography (GC) on 29 the commonly used polar capillary columns, less information is available on its occurrence and 30 distribution. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It was reported that c7-20:1 was a minor component in the total c-20:1 content of most pelagic fish, which is rich in either c11 or c9-20:1 isomers. In contrast, the c7-20:1 isomer was one of the major isomers contributing to the total c-20:1 content in benthic fishes and also their dietary animals 14 . In the current study, a high content of c7-20:1 was mainly recorded in benthic fish 28 .…”
Section: Distribution Of C-20:1 Isomers In Fishes From the Indian Oceanmentioning
confidence: 83%
See 4 more Smart Citations
“…It was reported that c7-20:1 was a minor component in the total c-20:1 content of most pelagic fish, which is rich in either c11 or c9-20:1 isomers. In contrast, the c7-20:1 isomer was one of the major isomers contributing to the total c-20:1 content in benthic fishes and also their dietary animals 14 . In the current study, a high content of c7-20:1 was mainly recorded in benthic fish 28 .…”
Section: Distribution Of C-20:1 Isomers In Fishes From the Indian Oceanmentioning
confidence: 83%
“…2 and 12 and Nakamura et al 14 for the same GC column and Ando and Sasaki 15 for the SLB-IL100 GC column. The IS c14-20:1 eluted Fig.…”
Section: Percentage Of Lipid Contentmentioning
confidence: 88%
See 3 more Smart Citations